Special issue: Update on neural oscillations in neuropsychiatric disorders - Güntekin, Bahar; O’Donnell, Brian F. (SAGE Publications Inc., 2023)
The present issue highlights recent progress in the analysis of oscillatory activity for the assessment, understanding and remediation of psychiatric and neurologic disorders. Contemporary interest in neural synchrony and oscillations in neuropsychiatric disorders has been motivated by investigations of cellular and network oscillations, modeling of neural networks and advances in signal analysis. Hebb1 proposed that synchronous activation between two neurons strengthened connectivity between them; and that a reverberatory neural circuit could maintain a representation of a stimulus in memory. More recent findings implicate neural synchrony and oscillations in feature binding, attentional selection, arousal, memory operations and consciousness.2-9 Consequently, disturbances of oscillations within and between neural ensembles may contribute to sensory, behavioral and cognitive deficits in neuropsychiatric disorders. Because human EEG and MEG activity are generated by synchronized inhibitory and excitatory post-synaptic potentials within large ensembles of neurons, they are well suited for the detection of neural synchrony and oscillations with millisecond temporal resolution.
Keywords: Neuropsychiatric Disorders; Neural Oscillations; Special Issue